Edukacja we współpracy w perspektywie na nowo odczytywanych założeń teoretycznych oraz wyzwań społecznych - Bąbka, Jarosław (Studia Edukacyjne, 2019)
Scientific output of psychology and education studies, paradigmatic changes and social expectations form a basis for rereading the assumptions of cooperative education. The paper deals with the categories of recognizing cooperative education as an organizational form, a strategy of teaching and a model of education. The paper makes a reference to the assumptions resulting from the social-constructive paradigm, which have made it possible to present a way of thinking about cooperative education in terms of joint acquisition of knowledge and negotiating meaning. The sources of the assumptions of education were also investigated in the ideology of progressivism to show that such upbringing and education helps develop pupils’ social competencies and prepares the students for functioning in a community. The considerations are completed by showing a relation between cooperative education and contemporary social challenges.